Decision-making process of PROCSERV a case study of the small group communication - Young, Rosa May D.
This study was conducted in order to explore the group process of the Board of Directors of the Professional Customer Service Cooperative of Davao during their Board of Directors meeting. By recording the meeting and through process observation analysis, various aspects of the group dynamics such as decision-making process, communication, participation, individual tools, behavior and leadership were discussed and analyzed. The communication patterns of the group were observed to be very flexible. The group atmosphere ideally has an important role in influencing the participation, behavior, and communication environment in the meeting. The group?s inato style was effective for them because it gave them the freedom to articulate and express their ideas, opinions, and feelings as well. The study in a way gives the people an understanding about group process especially in the Philippine context and how the formal process was redefined. Despite the seemingly informal way that the group handled their meeting, they were able to make sound decisions concerning the different issues.